Desmoid-type fibromatosis of the breast: a case report and literature review - Zhao, Zijun; Shang, Qingyao; Yang, Chenxuan; Liu, Jiaxiang; Liu, Shanqing; Li, Xiaoqian; Kang, Xiyu; Yue, Jiaxian; Wang, Xin; Wang, Xiang (Frontiers in Oncology, 2025)
Breast desmoid-type fibromatosis (BDF) is a rare tumor predominated by mesenchymal cells. It has a high recurrence rate, although distal metastasis is uncommon. It resembles breast cancer clinically, and histological pathology is the only approach to a confirmed diagnosis. Comprehensive and individualized treatments were recommended for BDF patients. Here, we presented a case of BDF secondary to primary breast carcinoma in our center. A 47-year-old female complained of a large mass in her left breast for 2.5 months. She has a past history of left breast carcinoma with a failure of surgical and systemic intervention. Despite an active re-operation, she still suffered from disease progression with a bad prognosis. After our report, the clinicopathological traits, differential diagnosis of BDF and current recommendation of management were discussed. This case report aimed to make a clear recognition of this rare and aggressive disease and elaborate up-to-date treatment recommendations. More effective drugs and larger sample clinical studies are encouraged for better management of refractory and progressive BDF.